PD-1 inhibitor sintilimab treated patients with metastatic triple-negative breast cancer - Jia, Yan; Zhang, Jie; Shi, Yehui; Dong, Guolei; Guo, Xiaojing; Tong, Zhongsheng (Frontiers in Cell and Developmental Biology, 2024)
Purpose: Triple-negative breast cancer is highly challenging subtype due to unique tumor microenvironment. Several evidences (IMpassion130 and KEYNOTE-355 trial) supported therapeutic effect of immune checkpoint inhibitor in TNBC. However, the efficacy and safety of PD-1 inhibitor sintilimab in breast cancer has not been well investigated. So, data of sintilimab treated patients with metastatic BC was collected and analyzed in this study. Methods: The patients were eligible according to the requirements included: ages between 18 years and 75 years; recurrent or metastatic TNBC; measurable disease based on RECIST v1.1; no limitation on the prior systemic treatments; and ECOG performance status of 0 to 1. Patients received sintilimab 200mg intravenously every 3 weeks until unacceptable toxicity or disease progression. Results: From June 1, 2019 to October 1, 2022, 40 female patients (median age, 55.5 years) with metastatic TNBC were enrolled into study. The median prior lines of systemic therapy for mTNBC was three (range, 1-8), with 60% of cases had received at least three lines of therapy for metastatic disease. The visceral or brain metastasis was detected in 40.4% or 9.6% of patients, separately. The median duration of response was 2.8 months (range, 0.7 to 21.0), and median number of sintilimab doses administrated was 4 (range, 1 to 30). The ORR and DCR were 22.5% and 72.5%. The median PFS was 3.5 months (range, 1.4 to 21.0), with a 6-month PFS rate of 15.0% (6/40). The median OS was 52.5 months (range, 9.0 to 247.0) as of data cut-off. Common adverse effects were acceptable, fatigue, skin rash and pruritus were the frequent toxicity observed. Two cases of grade 3 curable adverse events were considered as treatment-related. PD-L1-positive tumor was found in 40% cases (4/10) of mTNBC. Although statistical difference was not reached, the trend was obvious. Patient with PD-L1-positive tumor gained better treatment response, while TMB-high carrier received more benefit of PFS and OS. Conclusion: The preliminary evidence was provided about the anticancer activity and acceptable adverse effects of sintilimab administrated every 3 weeks to pretreated patients with mTNBC. Sintilimab showed its efficacy and safety of immunotherapy for patients with advanced TNBC.